Marxsche Theorie und Imperialimus - Milios, Jannis; Sotiropoulos, Dimitris P. (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2010)
For more than a century ‘imperialism’ has been a key concept in theoretical discussions and politics, never denoting a single theoretical approach. In classical Marxist theories imperialism was seen as the notion deciphering capital’s global trajectories, to the extent that the different nation-states were not fading away despite the global character of capitalism. Many subsequent narratives of international capitalism represent alternative attempts at conceptualizing the very same problem of the ‘lack of correspondence’ between the territory of the national state on the one hand and the sphere of operations of capital. In our view, all these theoretical strategies share a common point of departure: namely, the rejection of the Marxian concept of social capital. This rejection has significant consequences for the way of understanding how class power is organized within a social formation and so the way in which we should understand imperialism. The concept of the imperialist chain opens up a fertile theoretical terrain in an endeavor to extend the Marxian problematic.